Análise de insolvência empresarial : uma abordagem financeira fundamentalista com aplicação do método estatístico multivariado e da técnica discriminante - Mateus, Regis Santos (2010)
The insolvency business represents an excellent subject for a wide and diverse range of economic agents and may be the result of complex internal and external factors to the company. Considering these factors, it is assumed the assumption that fundamental analysis fulfills an important role in addressing these issues, whether in character microeconomic or macroeconomic context. In order to investigate the influence and behavior of these factors, identified from the macroeconomic, sectoral, and the fundamentals of companies, we use the statistical method and technique of multivariate discriminant analysis. The main restrictive assumption concerns the relevance of including variables other than those normally used in forecasting models of corporate insolvency. The investigation process is delimited as follows: in spatial terms of specificity and covers large companies with a designation of SA (corporation) a publicly traded operating in Brazil. The time frame considered the year 2008 and covers the macroeconomic and microeconomic variables. And as research design considers the observational study in conjunction with the application of multivariate statistical method and by the statistical technique of discriminant analysis. Given the various studies related to prediction of bankruptcy that are very similar to this research, probably the significance of financial ratios representing the predictor variables normally used in the discriminant model variables and distinctly included in this analysis is relatively similar, where the statistical significance of each of these variables is coherent and consistent in the analysis of insolvency of Brazilian companies.